2011
DOI: 10.1016/j.biopha.2011.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch-mediated error prone repair at the immunoglobulin genes

Abstract: The generation of effective antibodies depends upon somatic hypermutation (SHM) and class-switch recombination (CSR) of antibody genes by activation induced cytidine deaminase (AID) and the subsequent recruitment of error prone base excision and mismatch repair. While AID initiates and is required for SHM, more than half of the base changes that accumulate in V regions are not due to the direct deamination of dC to dU by AID, but rather arise through the recruitment of the mismatch repair complex (MMR) to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 152 publications
(188 reference statements)
2
29
0
Order By: Relevance
“…As for Ung, Pms2 and Mlh1 deficiencies have been reported to have no impact on A/T mutagenesis (9). More recent data, obtained using catalytic knock-in mutants, further addressed the specific contribution of the endonuclease activity of Pms2 and did not report any major impact of its inactivation on Ig gene hypermutation (21).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…As for Ung, Pms2 and Mlh1 deficiencies have been reported to have no impact on A/T mutagenesis (9). More recent data, obtained using catalytic knock-in mutants, further addressed the specific contribution of the endonuclease activity of Pms2 and did not report any major impact of its inactivation on Ig gene hypermutation (21).…”
Section: Discussionmentioning
confidence: 87%
“…This pathway generates mainly mutations at A/T bases distal to the initial deamination sites, because of the specific error-proneness of Pol, which copies Ts with low fidelity. This patch repair is unusual in that the second part of the mismatch repair complex, MutL␣, composed of Pms2 and Mlh1, appears to be dispensable and relies on the sole Msh2-Msh6 complex (MutS␣) together with ExoI (8,9). Therefore, which endonuclease activity provides the DNA incision required to initiate error-prone synthesis is not completely clear.…”
mentioning
confidence: 99%
“…It now appears that PCNA monoubiquitylation is generally induced when DNA damage (uracil, O 6 -methylguanine) occurring outside of S-phase activates MMR, which generates long excision tracts that cannot be readily filled in by high-fidelity polymerases . The latter findings provide a possible explanation for the involvement of MMR proteins in antibody maturation, where-counterintuitively-they are required for immunoglobulin mutagenesis, rather than for its prevention (Chahwan et al 2011;.…”
Section: Mmr Proteins In Other Pathways Of Dna Metabolismmentioning
confidence: 94%
“…Mouse genetic experiments clearly demonstrated that SHM requires, in addition to MSH2 [50], MSH6 [51], EXO1 [52] and polymerase-η [53,54] also mono-ubiquitylated PCNA [55]. As SHM mutations at T/A base pairs are reduced to a similar extent in knock-in mice expressing a non-ubiquitylatable PCNA K164R variant, and in Msh2 -/-or Msh6 -/-animals [55], the origin of the mutations appears to be monoubiquitylated PCNA-mediated recruitment of error-prone DNA polymerases to MMR-generated gaps (see for [56] recent review). Why the processing of AID-generated U/G mispair might trigger PCNA ubiquitylation and error-prone DNA synthesis, rather than deploy error-free replicative polymerases is currently the subject of intense study in several laboratories.…”
Section: Mmr Proteins In Antibody Maturationmentioning
confidence: 99%